Organoleptic Study of Red Dragon Fruit Jam (Hylocereus polyrhizus) from the Perspective of Statistics and Food Chemistry - Lestari*, Mega Fia; Utami, Hermin Hardyanti; Yusriadi, Yusriadi; Desa, Susilo Sudarman (Universitas Syiah Kuala, 2025)
Red dragon fruit (Hylocereus polyrhizus) based jam products have high potential, but consumer acceptance is still limited due to sensory constraints that arise when dragon fruit skin is used as an additional ingredient. This study aimed to evaluate the sensory quality of red dragon fruit jam by adding dragon fruit peel, using statistical and food chemistry approaches. Organoleptic tests were conducted on 30 untrained panellists to assess four main attributes: colour, texture, odour, and taste, using a 9-point hedonic scale. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the one-sample t-test, and cronbach's alpha reliability test. The results showed that colour and texture were not significantly different from the